Mesoscale aspects of atmospheric flow in complex orography - Hálfdán Ágústsson 1977- (2015)
The weather and climate in Iceland is to a large degree governed by synoptic scale weather systems and orographic forcing. This thesis is composed of 15 peer-reviewed papers pertaining to atmospheric processes in complex terrain, with a special focus on Iceland. Severe weather is the subject of most of the papers, either in the context of primary weather parameters such as wind, or in relation to secondary parameters such as atmospheric turbulence and icing. In two papers, numerical simulations and observations of winds are used to map and analyze katabatic winds during a heatwave in South-Iceland as well as near the Hofsjökull ice cap in central Iceland. Observations of weak orographically forced winds are also the subject of another paper where asymmetric atmospheric vortices are shed in the lee of a large mountain in West-Iceland and advected 120 km towards and over Reykjavík. Five papers analyze simulations and observations of winds during severe windstorms in Southeast- and Northwest-Iceland. The performance of the atmospheric model with regard to model setup and the parameterizations of moisture physics and boundary layer processes is investigated and analyzed in two of the papers. The strongest winds are generally found below amplified and/or breaking gravity waves, as well as hydraulic jump-like features, on the lee side of large mountains. The papers reveal the importance of high horizontal resolution for resolving downslope windstorms in complex terrain and that interpolation from coarse-resolution simulations may lead to large errors, even if the mountains are to some extent correctly reproduced. The downstream extent of downslope windstorms depends strongly on the upstream structure of the atmosphere and its prediction is one aspect of numerical weather prediction that needs improvement. These papers also reveal that fine scale numerical simulations are not only needed to capture windstorms at the surface in complex terrain but also to correctly reproduce turbulence aloft, both at lower tropospheric ...